Teratogenic agents and fetal development: A narrative review (Research, Society and Development, 2021)
Worldwide, according to the Global Report on Congenital Defects, about 7.9 million babies - 6% of all births - have at birth some congenital malformation of genetic or partially genetic origin, while hundreds more are born with developed congenital malformations, preventable causes. The estimated value of the causes of non-genetic malformations is estimated at around 5 to 10%, mainly associated with maternal exposure to teratogenic agents, such as medication, alcohol, tobacco, illicit drugs, microorganisms, radiation, environmental pollution, among others. Thus, this study aimed to identify the influence of some of the main chemical and biological teratogenic agents on congenital malformations, through a narrative literature review.